Effect of starch and lignin on physico‐chemical properties of phenol–starch resin and its resin core sand1. Issue 7 (26th February 2013) - Zhang, Lihong; Zheng, Yuying; Zhang, Youfang; Lin, Tao
Abstract: A novolac like phenolic resin was prepared by copolymerization with phenol and hydrolyzed starch as the substitute for formaldehyde under catalysis of sulfuric acid. Liquefied phenolated lignosulfonate was introduced to the phenol–starch resin in this study as a partial phenol substitute. The phenol–formaldehyde resin, phenol–starch resin, and lignin–phenol–starch resin were characterized with lab standard analysis for their physicochemical specifications such as solid content, gel time, softening point, viscosity, and free phenol content according to corresponding Chinese National Standards. Mechanical properties of modified and unmodified resin core sand were investigated. Structures of modified and unmodified resins were characterized with infrared spectrum analysis (FTIR) and carbon‐13 NMR spectrometry ( 13 C NMR), while their thermal properties were studied with thermogravimetric analysis (TGA) and DSC. The modified resin and its core sand have acceptable physicochemical specifications, thermal resistance and mechanical properties as compared with unmodified resin and phenol–formaldehyde resin.